Screening of Some Botanicals for Eco-friendly Control of Cucurbit Fruit Fly (Bactrocera cucurbitae) Infestation in Experimental Cucumber Field (Journal of Environmental Science and Natural Resources, 2022)
Cucurbit fruit fly (Bactrocera cucurbitae) is the major pest of Cucumber (Cucumis sativus L.), which severely damage the cucumber production. This study was carried to evaluate the efficacy of fourteen botanicals such as Chili (Capsicum frutescens), Garlic (Allium sativum), Onion (Allium cepa), Ginger (Zingiber officinale), Carrot leaves(Daucuscarota subsp. Sativus), Bitter gourd (Momordic acharantia), young Tomato (Solanum lycopersicum), Mahogany seed (Swietenia macrophylla), Eucalyptus leaves (Eucalyptus globulus), Black plum leaves (Syzygium cumini), Jackfruit leaves (Artocarpus heterophyllus), Neem leaves (Azadirachta indica), Black pepper (Piper nigrum) and Garden croton leaves (Codiaeum variegatum) to control the cucurbit fruit fly infestation in experimental cucumber (Green Rohini F1 Hybrid Cucumber) field during March 15, 2021– May 14, 2021. This study observed a less number of cucurbit fruit fly attack on cucumber fruits in Ginger treatment. In this treatment, only 7.06% fruits were infested by cucurbit fruit fly. The Ginger treatment reduced 14.17 times fruit fly infestation compare to control. However, a high number of cucurbit fruit fly infestations were found in Bitter gourd, young Tomato, Mahogany and Garden croton treatments. Cucurbit fruit fly infestation was low (12.50%) in Neem treatment. This treatment showed best performance on cucumber size (cm) and yield (gm). The lowest yield was found in Bitter gourd treatment. The Neem treatment kept about 3.54 times better performance in respect to cucumber yield than that of control treatment. Therefore, Neem leaves (Azadirachta indica) and Ginger (Zingiber officinale) extracts can be used as bio-pesticide for eco-friendly control of cucurbit fruit fly infestation in cucumber field.Environ. Sci. & Natural Resources, 13(1&2): 38-42, 2020